Power elite in India - Gupta, Khadija Ansari, (ed.) (New Delhi, 1989)
The theme of 'Power elite' bristles with controversies. It at once brings to the fore the debate between the Marxists and the empiricists. When Pareto, Mosca and Michels advanced the concept of elite as a contribution to the theory of political sociology, they claimed to be empirical social scientists as distinct from the Marxists. While the Marxists emphasised the role of class, the empiricists stressed the role of elite in society. The elite paradigm saw power-politics tied to group- interests and, indeed, in time the term 'elite' became narrowly co-terminous with power and its operations. The Marxists, on the other hand, held the view that any study of group-conflict among elites helped little to facilitate under- standing of the structures of society wherein power and au- thority and the substance of juridical-legal system were lo- cated. Besides, the empiricist concept of power elite was too static and a-historical. Paretos' theory of "circulation of elite" (between the in and out-groups) failed, according to the Marxists, to analyse transition of society from one epoch to another.
Keywords: Elite (Social Sciences) India